Optimization and Physical Stability of Toothpaste Preparations Essential Oils of Thyme (Thymus Vulgaris L.) and Peppermint (Mentha piperita L.) With SLD (Simple Latix Design) - Latifah, Fadzil; Sholeh, Aries Badrus; Rofiah, Khafidhotur (BENCOOLEN JOURNAL OF PHARMACY, 2025)
Thymus vulgaris L. essential oil contains the active compound thymol which has the potential as an antimicrobial, and peppermint essential oil contains menthol which has the potential to reduce the growth of Streptococcus mutans microorganisms. Based on the properties of these two ingredients, it is formulated in the form of toothpaste preparations. Methods method used quantitative research with laboratory experimental research Design using SLD (Simple Latix Design) with varying concentrations of Na CMC and SLS. SLD results results of 8 formulas obtained the optimum formula at a concentration of 1% NaCMC and 2% SLS and a result of 1,000. desirabiliti 1.000. Predictions based on SLD obtained a viscosity test of 21364.2 cPs, pH 9.00303, spreadability 4.3021 cm, and spreadability 4.3021 cm. Spreadability 4.3021 cm, foam height 12.6535 mm and One sample t test results (p>0.05) showed the results were not significantly different. showed the results were not significantly different. The results of the stability test for 3 cycles were tested organoleptical test has a white color, a distinctive smell of mint, a semi-solid texture and does not change for 3 cycles. changes for 3 cycles, ph test, spreadability test, foam height test and voiscosity test show results in accordance with the requirements based on the One Way ANOVA test results show (p>0.05) which means the results are not significantly different for 3 cycles. means the results are not significantly different for 3 cycles. In conclusion, all formulasin this study meet the required criteria for toothpaste preparations and the most optimum paste consistency is the Na variation. The most optimum paste consistency is the variation of Na CMC 1% and SLS 2%.